Societal costs of permanent childhood hearing loss at teen age: a cross-sectional cohort follow-up study of universal newborn hearing screening. Issue 1 (24th February 2018) - Chorozoglou, Maria; Mahon, Merle; Pimperton, Hannah; Worsfold, Sarah; Kennedy, Colin R
Abstract : Objective: To investigate the effects in adolescence of bilateral permanent childhood hearing loss (PCHL) > 40 dB and of exposure to universal newborn hearing screening (UNHS) on societal costs accrued over the preceding 12 months. Design, setting, participants: An observational cohort study of a sample of 110 adolescents aged 13–20 years, 73 with PCHL and 37 in a normally hearing comparison group (HCG) closely similar in respect of place and date of birth to those with PCHL, drawn from a 1992–1997 cohort of 157 000 births in Southern England, half of whom had been exposed to a UNHS programme. Intervention: Birth in periods with and without UNHS. Outcome measures: Resource use and costs in the preceding 12-month period, estimated from interview at a mean age of 16.9 years and review of medical records. Effects on costs were examined in regression models. Results: Mean total costs for participants with PCHL and the HCG were £15 914 and £5883, respectively (difference £10 031, 95% CI £6460 to £13 603), primarily driven by a difference in educational costs. Compared with the HCG, additional mean costs associated with PCHL of moderate, severe and profound severity were £5916, £6605 and £18 437, respectively. The presence of PCHL and an additional medical condition (AMC) increased costs by £15 385 (95% CI £8532 to £22 238). An increase of one unit in receptive language z-score was associated with £1616 (95% CI £842 to £2389) lower costs. Birth during periods of UNHS was not associated with significantly lower overall costs (difference £3594, 95% CI −£2918 to £10 106). Conclusions: The societal cost of PCHL was greater with more severe losses and in the presence of AMC and was lower in children with superior language scores. There was no statistically significant reduction in costs associated with birth in periods with UNHS. Trial registration number: ISRCTN03307358, pre-results.